Queijo minas artesanal fresco de produtores não cadastrados da mesorregião de Campo das Vertentes - MG: qualidade microbiológica e físico-química em diferentes épocas do ano - Renata Dias de Castro (2015)
The production of artisanal Minas cheese is traditional in Minas Gerais. This cheese is made using raw cow' milk and endogenous culture. The artisanal Minas cheese presents a diverse microbiota influenced by region of the state where it is produced. There are few data about the microbiota present in this food. The aim of this study was to determine the microbiological and physical-chemical characteristics of artisanal Minas cheese produced by non-registered cheesemakers from Campos das Vertentes region, Minas Gerais, in two different seasons, rainy and dry seasons. Samples of water, raw milk, endogenous culture and cheese from rural properties were analyzed. In water, Aerobic Plate Count (APC) was higher (p <0.05) in the rainy season. However, the pH and residual chlorine was higher (p <0.05) in the dry season (p <0.05). There were not any differences on the Somatic Cell Counts (SCC) and Total Bacterial Count (TBC) in samples of milk when seasons were compared. The fat of the raw milk was higher (p <0.05) in the rainy season. The most probable number of total and thermotolerant coliforms was significant difference (p <0.05) in samples of raw milk and cheese. In endogenous culture, the most probable number of thermotolerant coliforms was higher (p<0.05) in the dry rainy season.The cheese exhibited higher counts of lactic acid bacteria, in M17 medium, molds and yeasts and higher acidity in the dry season (p <0.05). The cheeses exhibited high moisture regardless of the season. Staphylococcus spp. was found in high numbers in cheeses and Staphylococcus coagulase positive were higher (p <0.05) in cheese and endogenous culture during the rainy season. Fifty percent of artisanal Minas cheese handlers were carriers of Staphylococcus coagulase positive in their hands. Salmonella spp. were not detected in any sample inspected. High counts of lactic acid bacteria (LAB) were observed in all samples. Enterococcus faecalis was the most frequent (44%) species in milk, endogenous culture and cheese, followed by Lactococcus lactis (20%) and Lactobacillus plantarum (16%). Enterococcus durans, Enterococcus pseudoavium, Aerococcus viridans and Lactobacillus brevis were isolated from endogenous culture and it is probably the first description of these LAB in this product. These results indicated more contamination of samples in the rainy season. The seasons also influenced the physical and chemical parameters of water, raw milk and cheese. These results suggest the need of adjustments in the production of artisanal Minas cheese in order to guarantee a safe and competitive food, aside from being valorized for its traditional characteristics.